From AI Adoption to Social Venture Creation: A Qualitative Review of Cognitive Pathways Linking Generative AI Competencies to Digital Social Entrepreneurship - Siti Maulizah; Aura Nabila (LPPM STIE Kasih Bangsa, 2025)
This qualitative literature review examines how generative artificial intelligence (AI) competencies are cognitively transformed into digital social entrepreneurial intentions and social venture creation. Synthesizing recent interdisciplinary studies across artificial intelligence, entrepreneurial cognition, and social entrepreneurship, the review develops an integrative framework explaining the cognitive pathways linking AI adoption to social value–oriented digital entrepreneurship. Drawing on the Entrepreneurial Event Model and the Stimulus–Organism–Response perspective, the findings reveal that generative AI acts as a cognitive stimulus that enhances opportunity recognition, creative problem-solving, perceived feasibility, and perceived desirability of social ventures. The review further identifies key cognitive mechanisms through which AI competencies support ideation, opportunity evaluation, resource mobilization, and early-stage scaling of digital social enterprises. By positioning generative AI as a form of cognitive infrastructure rather than a mere technological tool, this study advances theoretical understanding of AI-enabled social entrepreneurship and offers insights for entrepreneurship education, policy design, and inclusive digital innovation ecosystems